Effectiveness of Manual Therapy and Stretching for Baseball Players With Shoulder Range of Motion Deficits. (May 2017) - Bailey, Lane B.; Thigpen, Charles A.; Hawkins, Richard J.; Beattie, Paul F.; Shanley, Ellen
Background: Baseball players displaying deficits in shoulder range of motion (ROM) are at increased risk of arm injury. Currently, there is a lack of consensus regarding the best available treatment options to restore shoulder ROM. Hypothesis: Instrumented manual therapy with self-stretching will result in clinically significant deficit reductions when compared with self-stretching alone. Study Design: Controlled laboratory study. Methods: Shoulder ROM and humeral torsion were assessed in 60 active baseball players (mean age, 19 ± 2 years) with ROM deficits (nondominant − dominant, ≥15°). Athletes were randomly assigned to receive a single treatment of instrumented manual therapy plus self-stretching (n = 30) or self-stretching only (n = 30). Deficits in internal rotation, horizontal adduction, and total arc of motion were compared between groups immediately before and after a single treatment session. Treatment effectiveness was determined by mean comparison data, and a number-needed-to-treat (NNT) analysis was used for assessing the presence of ROM risk factors. Results: Prior to intervention, players displayed significant ( P < 0.001) dominant-sided deficits in internal rotation (−26°), total arc of motion (−18°), and horizontal adduction (−17°). After the intervention, both groups displayed significant improvements in ROM, with the instrumented manual therapy plus self-stretching group displaying greater increases in internal rotation (+5°, P = 0.010), total arc of motion (+6°, P = 0.010), and horizontal adduction (+7°, P = 0.004) compared with self-stretching alone. For horizontal adduction deficits, the added use of instrumented manual therapy with self-stretching decreased the NNT to 2.2 (95% CI, 2.1-2.4; P = 0.010). Conclusion: Instrumented manual therapy with self-stretching significantly reduces ROM risk factors in baseball players with motion deficits when compared with stretching alone. Clinical Relevance: The added benefits of manual therapy may help to reduce ROM deficits in clinical scenarios where stretching alone is ineffective.